Unit 2.6: Open Educational Resources (OER) and MOOCs in online-oriented STEM teaching (Lecture Notes) - Teixeira, António (2022)
Objective 1: to recognise the different movements promoting openness in science research, innovation and education and identify synergies and interconnections between them. Objective 2: to characterize Open Educational Resources (OERs) and identify its typical features and contexts of use. Objective 3: to distinguish MOOCs according to different design patterns and select the most appropriate to each given learning need. Objective 4: to search, find and assess OERs and MOOCs for STEM teaching and learning situations. Objective 5: to implement Open Educational Practices in STEM teaching and learning.